Quality of cut and basecutter blade configuration for the mechanized harvest of green sugarcane (Scientia Agricola, 2013)
Quality control is used to evaluate processes and products, and is a powerful tool for reducing variability. The objective of this study was to evaluate the quality of green sugarcane (Saccharum spp.) cutting for mechanized harvest, using statistical quality control tools. Cutting height and damage to ratoon stalks caused by different blade and disc combinations of the basecutter mechanism were used as indicators of quality. Cutting height showed high variability with a controlled process for some treatments. However, these treatments were incapable of producing satisfactory results. The damage index was lower in treatments that used tilted blades, but above the target for all treatments, which caused significant damage to the ratoons. In general, the process of mechanized harvest as assessed by these indicators was found incapable of achieving targeted results and staying below specification limits, and thus requires corrective actions to improve quality.